Pengembangan Modul Berbasis Guided Inquiry Pada Pokok Bahasan Laju Reaksi - Ani Sutiani; Dinda Maisyarah (Universitas Negeri Medan, 2021)
This study aims to design a guided inquiry-based module on the subject of reaction rates and to analyze the feasibility of a guided inquiry-based module on the subject of reaction rates. The method in this research uses the research and development or Research and Development method which is limited to only 5 stages, namely the data and information collection stage, the product planning stage, the initial product development stage, the initial field trial stage and the revision stage of the trial results. The research subject was a guided inquiry-based module. The object of research was the material reaction rate. The product developed was validated by 4 expert validators consisting of 2 material expert validators and 2 media expert validators. In addition, the responses of 2 chemistry teachers were also seen. Initial field trials were carried out by giving questionnaire sheets to 8 students. The results showed that the guided inquiry-based module on the subject of reaction rates was declared feasible after validation by material experts, media experts, teacher and student responses. Evaluation of material experts with an average percentage of 83.10% with the valid / feasible category, the assessment of media experts with an average percentage of 83.09% with the valid / feasible category, the percentage of teacher responses to 87.49% with the very interesting category and the percentage of responses 83.08% students with very interesting category.